Causal relationship between matrix metalloproteinase and pulmonary embolism: a bidirectional two-sample Mendelian randomization study - Xiaowei Gong; Yadong Yuan (Scientific Reports)
Abstract This study evaluated the causal relationship between matrix metalloproteinases (MMPs) and pulmonary embolism using data from the genome-wide association study (GWAS) of pulmonary embolism from the UK Biobank and a GWAS dataset of MMPs based on 5,457 Icelanders aged 65 years and older. MR-Egger, MR-PRESSO, Cochran’s Q, and leave-one-out were used for sensitivity analysis. The Mendelian randomization (MR) analysis, based on the IVW analysis, indicated an elevated risk for pulmonary embolism in association with MMP19 (OR = 1.0009, 95%CI: 1-1.0017, P = 0.041), consistent with the weighted median method results (P = 0.015). In addition, despite the negative result from the IVW method (P = 0.554), the weighted median analysis suggested a reduced risk for pulmonary embolism related to MMP12 (OR = 0.9992, 95%CI: 0.9984-1, P = 0.038). No causal associations were found for the other MMPs (including MMP1, MMP2, MMP3, MMP7, MMP8, MMP9, MMP10, MMP13, MMP14, MMP16, MMP17, and MMP20) on pulmonary embolism (all P > 0.05). The reverse MR analysis revealed no causal associations between pulmonary embolism as exposure and MMPs as outcomes. Sensitivity analyses confirmed the robustness of these findings. In conclusion, this MR analysis revealed the potential causal relationship between MMPs and pulmonary embolism, suggesting that measuring MMPs could help identify people at higher risk of pulmonary embolism, but further research is needed.